Answer:
x = 1
Step-by-step explanation:
<em>Here's</em><em> your</em><em> solution</em>
<em>=</em><em>></em><em> </em><em>(</em><em>3</em><em>x</em><em> </em><em>-</em><em> </em><em>3</em><em>)</em><em>/</em><em>5</em><em> </em><em>=</em><em> </em><em>(</em><em>2</em><em>x</em><em> </em><em>-</em><em> </em><em>2</em><em>)</em><em>/</em><em>4</em>
<em>=</em><em>></em><em> </em><em>4</em><em>(</em><em>3</em><em>x</em><em> </em><em>-</em><em>3</em><em>)</em><em> </em><em>=</em><em> </em><em>5</em><em>(</em><em>2</em><em>x</em><em> </em><em>-</em><em> </em><em>2</em><em>)</em>
<em>=</em><em>></em><em> </em><em>1</em><em>2</em><em>x</em><em> </em><em>-</em><em> </em><em>1</em><em>2</em><em> </em><em>=</em><em> </em><em>1</em><em>0</em><em>x</em><em> </em><em>-</em><em> </em><em>1</em><em>0</em>
<em>=</em><em>></em><em> </em><em>2</em><em>x</em><em> </em><em>=</em><em> </em><em>2</em><em> </em>
<em>=</em><em>></em><em> </em><em>x </em><em>=</em><em> </em><em>2</em><em>/</em><em>2</em>
<em>=</em><em>></em><em> </em><em>x </em><em>=</em><em> </em><em>1</em>
<em> </em><em> </em><em> </em><em> </em><em>hope</em><em> it</em><em> helps</em>